IMPLEMENTASI MEDIASI PADA PROSES PERCERAIAN TKI DI PENGADILAN AGAMA PONOROGO - Taufiqurohman Taufiqurohman (Institut Agama Islam Negeri Batusangkar, 2021)
This paper discusses the implementation of mediation in the Indonesian Worker (TKI) divorce process at Religious Court of Ponorogo. Recently, mediation has become an alternative in resolving cases outside the litigation path. The high number of divorce cases is increasingly concerning, for example in 2013, Religious Court of Ponorogo experienced an increase of 1,781 cases from 1,668 cases in 2012. After six years, the divorce rate is still quite high. Data for 2019 for the period of January-August, 422 cases of divorce, and 1,044 cases of divorce doubled. The cause of the divorce is mostly due to economic factors, the continuous bickering until these factors leave one party. Interestingly, cases of divorce include a married couple who work as migrant workers. Mediation as an important instrument in divorce prevention, as well as part of the court process, is the starting point for handling divorce for migrant workers. However, the existence of the parties because they work as migrant workers certainly has implications for the implementation of mediation. The approach used is a normative juridical approach, namely an approach based on the provisions of Islamic law and statutory regulations. As a result, TKI mediation in Religious Court of Ponorogo in 2013 reached 104 cases, all of which ended in failure. In addition, out of 104 cases, 81 cases were decided one after another because one party never attended and was abroad.